Recuperación del bosque en el Premontano Húmedo y Muy Húmedo del Cantón de Mora, Costa Rica - Fournier O., Luis A.; Herrera de Fournier, María E. (Revista de Biología Tropical, 1985)
Secondary forest succession was studied in two old fields in Ciudad Colón and Tabarcia. Costa Rica (Premontane Moist Forest and Premontane Wet Forest, respectively). In both sites, after 10 years, nearly 70% of the tree families and 50% of the species were able to colonize an area of 1 ha in the center of a 1 km2 plot. Forest succession proceeds at a tapid rate in this region and after 20 years, 34 families and 84 species became established in the Ciudad Colón plot. The same trend was observed in Tabarcia. Apparently, the higher floristic diversity observed here, as compared to wetter tropical zones, could be explained on the basis that an increase in the limiting factors of the environment seems to favor the establishment of a higher number of pioneer and early successional tree species.